Artificial generation : photogenic French literature and the prehistory of cinematic modernity - Parker-Flynn, Christina (Rutgers University Press, 2022)
"Artificial Generation: Photogenic French Literature and the Prehistory of Cinematic Modernity looks at nineteenth-century literary representation and film theory, arguing that the depth of amalgamation that occurred within literary representation during this era is a key aesthetic tradition that continues to inform movies and contemporary culture today. A key part of this evolution in representation, a wide-scale artistic subjectivity around the re-emergence of the "artificial woman"-a notion that harkens back to longstanding expressions of mythological masculine subjectivity through the figure of the woman, refashioning important female figures that symbolize or problematize man's origins, including Eve and the Venus de Milo. This quest for masculine artistic subjectivity becomes a photographic and filmic drive by the turn of the century. The book explores the perpetuation of the myth of Pygmalion and Galatea in nineteenth-century literature. It then begins at the beginning of film history, with Georges Méliès in the 1890s and other "silent" filmmakers, moving through Alfred Hitchcock's Vertigo (1958) and Bladerunner 2049 (2017), analyzing these twentieth-century films to illustrate how these film texts are structured around mythic and literary principles from the prior century that serve as the basis for film as medium-a phantom form for life's representation. The book provides a crucial reassessment of the longstanding, mutual exchange between cinematic and literary representation, offering a fresh perspective on the proto-cinematic imperative of simulation within nineteenth-century literary symbolism"--